Культурні герої НТУ "ХПІ": Марк Рейзен - Міщенко, Марина Миколаївна (НТУ "ХПІ", 2016)
Дана стаття стосовно життя і творчості відомого оперного співака Марка Осиповича Рейзена є складовою проекту, що проводить кафедра етики, естетики та історії культури Харківського політехнічного інституту під назвою «Культурні герої НТУ «ХПІ». Метою цього проекту є вивчення внеску студентів та викладачів ХПІ в культурне життя епохи. Харківський Політех має ряд своїх видатних людей – «культурних героїв» – в архітектурі, літературі, музиці, театральному мистецтві. Прикладом досягнення значної творчої висоти є Марк Рейзен, чий талант виявився в Політехнічному інституті, розкрився в Харківській консерваторії і підкорив світ.

This paper deals with life and work of the famous opera singer Mark Osipovich Reizen as a part of the project, which holds by the department of ethics, aesthetics and cultural history of the Kharkiv Polytechnic Institute under the title "Cultural Heroes NTU "KHPI". The aim of this project is to study the contribution of students and teachers of Kharkiv Polytechnic Institute in cultural life of era. Kharkov Polytechnic University has a number of prominent people whom we can named "cultural heroes" in architecture, literature, music, theater arts. Mark Reizen is an example of achieving of considerable height level whose talent has appeared at the Polytechnic Institute, was revealed in Kharkіv Conservatory and conquered the world.
Cultural Нeroes of NTU "KHPI": Mark Reyzen
Keywords: мистецтво оперне; вокал академічний; майстерність акторська; образ сценічний; психологія творчості; opera; academic vocal; acting; stage image; psychology of creativity